2015
DOI: 10.1186/s13014-015-0498-1
|View full text |Cite
|
Sign up to set email alerts
|

Determining appropriate timing of adaptive radiation therapy for nasopharyngeal carcinoma during intensity-modulated radiation therapy

Abstract: BackgroundTo determine appropriate timing of an adaptive radiation therapy (ART) replan by evaluating anatomic and dosimetric changes of target volumes and organs at risk (OARs) during intensity-modulated radiation therapy (IMRT) for nasopharyngeal carcinoma (NPC).MethodsNineteen NPC patients were recruited. Each patient had repeat computed tomography (CT) scans after each five fractions and at treatment completion. Automatic re-contouring the targets and OARs by using deformable registration algorithm was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 25 publications
4
68
0
1
Order By: Relevance
“…While different numbers of replannings aimed at sparing the PG have been investigated in the literature, the optimal timing of these replannings has not been thoroughly assessed [8,13,15,16,[25][26][27][28][29][30][31][32][33][34]. The endpoint of these studies was the quantification of the dosimetric benefit of sparing the PG, while keeping or even increasing the minimum dose in the PTV, using different CT-based IMRT replanning scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…While different numbers of replannings aimed at sparing the PG have been investigated in the literature, the optimal timing of these replannings has not been thoroughly assessed [8,13,15,16,[25][26][27][28][29][30][31][32][33][34]. The endpoint of these studies was the quantification of the dosimetric benefit of sparing the PG, while keeping or even increasing the minimum dose in the PTV, using different CT-based IMRT replanning scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment plan adaptation can be used to prevent severe dose degradation throughout the fractionated treatment course11 and is related with lower normal tissue complication probabilities 12. For IMRT treatment, up to two adaptation steps was reported to be sufficient and is logistically feasible 13, 14, 15, 16. Adaptive IMRT has been shown to be associated with improved locoregional control,17 especially for advanced tumor stages 18…”
Section: Introductionmentioning
confidence: 99%
“…2 Hansen et al 7 found increased maximum doses to the brains stem occurred in 85% of patients, and all patients had increased maximum doses to the spinal cord, if adaptive replanning was not considered. Another study by Fung et al showed that the actual delivered doses to all listed OARs were higher than expected.…”
Section: -13mentioning
confidence: 99%
“…2 Briefly, GTVnx and GTVnd included the primary gross volume and the involved cervical lymphadenopathy, respectively, determined by the imaging, clinical, and endoscopic findings. The high-risk clinical target volume (CTV1) was defined as GTVnx plus 5-mm margin and entire nasopharyngeal mucosa plus 5-mm submucosal volume.…”
Section: Delineation Of the Targets And Oarsmentioning
confidence: 99%
See 1 more Smart Citation